2022
DOI: 10.1088/2040-8986/ac7e5a
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable InP waveguide components using the Sb2S3phase change material

Abstract: Reconfigurable waveguide components are promising building blocks for photonic neural networks and as an optical analogue to field-programmable gate arrays. By changing the effective index of the waveguide, reconfigurable waveguide components can achieve on-chip light routing and modulation. In this paper, we design and demonstrate an Sb2S3-reconfigurable InP membrane Mach–Zehnder interferometer (MZI) on a silicon substrate. Sb2S3, which has tunable refractive index and low absorption in the near-infrared spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Based on these results, we recommend the use of a ZnS-SiO 2 cap with at least a 30 nm thickness to protect Sb 2 S 3 and Ag-SbS films in PIC devices. Note, the optimized capping thickness would be applicable to most Sb 2 S 3 and Ag-SbS-tuned photonic devices as the corresponding PCM thickness is usually around or less than 30 nm. ,, Moreover, it is also possible for the 30 nm cap to preserve a thicker PCM layer. Previous literature had reported switching cyclability of up to 7000 times in 60 nm Sb 2 S 3 films capped in thinner Al 2 O 3 films (<60 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these results, we recommend the use of a ZnS-SiO 2 cap with at least a 30 nm thickness to protect Sb 2 S 3 and Ag-SbS films in PIC devices. Note, the optimized capping thickness would be applicable to most Sb 2 S 3 and Ag-SbS-tuned photonic devices as the corresponding PCM thickness is usually around or less than 30 nm. ,, Moreover, it is also possible for the 30 nm cap to preserve a thicker PCM layer. Previous literature had reported switching cyclability of up to 7000 times in 60 nm Sb 2 S 3 films capped in thinner Al 2 O 3 films (<60 nm).…”
Section: Resultsmentioning
confidence: 99%
“…These properties can influence the device design and switching operations. We chose to focus on Sb 2 S 3 as it exhibits the lowest optical loss among the four PCMs, Ge 2 Sb 2 Te 5 , Ge 2 Sb 2 Se 4 Te 1 , Sb 2 Se 3 , and Sb 2 S 3 , and consequently it is of particular interest for tuning a wide range of photonic devices. ,, ,,, Previously, we showed that lightly doping Sb 2 S 3 with Ag can lower the crystallization temperature and produce smaller crystallites. , The melting point for lightly Ag-doped Sb 2 S 3 (below 12.5%) along the Sb 2 S 3 –Ag 2 S tie line is also lower, suggesting a lower amorphization temperature. For these reasons, we believe that Ag-doped Sb 2 S 3 has potential applications in tunable photonic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing patterned PCMs in metasurface design is an excellent strategy to obtain a dynamic wavefront control. Despite the great success of GST in reconfigurable meta-devices within the infrared regime, the unconventional Sb 2 S 3 material with a large bandgap of 1.70∼2.05 eV shows a relatively low absorption in the visible spectrum around 600 nm 58,67 .…”
Section: B Phase Modulation In the Far Fieldmentioning
confidence: 99%
“…Through thermal or laser irradiation stimuli, PCMs can be reversibly switched between their amorphous and crystalline phases, resulting in a modulation of their refractive index in ultra-short times (of the order of ps) [ 37 , 38 , 39 ]. Therefore, the integration of PCMs in photonics gives an extra degree of freedom to tune their optical response post-fabrication [ 40 , 41 ]. For example, de Galarreta et al [ 42 ] proposed a new hybrid PCM-HRI metasurface concept in which active control is achieved by embedding deeply subwavelength inclusions of a tunable PCM (in this case Ge 2 Sb 2 Te 5 , i.e., GST) within the body of high-index Si nanocylinders.…”
Section: Introductionmentioning
confidence: 99%